Siza, Herández Léon, Riaño, Rueda y Terán : Remodelación del eje Prado-Recoletos (2003)
Proyectos de intervenciones para los <Juegos Olímpicos> 2012 en Madrid.
Keywords: MADRID; ESPAÑA; SIZA, ALVARO; HERNÁNDEZ LEÓN, JUAN MIGUEL; RENOVACION URBANA; CALLES; URBANISMO; PROYECTOS; INTERVENCIONES; RIAÑO, CARLOS DE; TERÁN, FERNANDO DE; RUEDA, JOSÉ MIGUEL